Two-Dimensional Transition Metal Boride TMB12 (TM = V, Cr, Mn, and Fe) Monolayers: Robust Antiferromagnetic Semiconductors with Large Magnetic Anisotropy - Huiqin Zhang; Nini Guo; Ziyu Wang; Yuqi Xiao; Xiangfei Zhu; Shu Wang; Xiaojing Yao; Yongjun Liu; Xiuyun Zhang (Molecules, 2023)
Currently, two-dimensional (2D) materials with intrinsic antiferromagnetism have stimulated research interest due to their insensitivity to external magnetic fields and absence of stray fields. Here, we predict a family of stable transition metal (TM) borides, TMB12 (TM = V, Cr, Mn, Fe) monolayers, by combining TM atoms and B12 icosahedra based on first-principles calculations. Our results show that the four TMB12 monolayers have stable antiferromagnetic (AFM) ground states with large magnetic anisotropic energy. Among them, three TMB12 (TM=V, Cr, Mn) monolayers display an in-plane easy magnetization axis, while the FeB12 monolayer has an out-of-plane easy magnetization axis. Among them, the CrB12 and the FeB12 monolayers are AFM semiconductors with band gaps of 0.13 eV and 0.35 eV, respectively. In particular, the AFM FeB12 monolayer is a spin-polarized AFM material with a Néel temperature of 125 K. Moreover, the electronic and magnetic properties of the CrB12 and the FeB12 monolayers can be modulated by imposing external biaxial strains. Our findings show that the TMB12 monolayers are candidates for designing 2D AFM materials, with potential applications in electronic devices.